ANALISIS TERHADAP PERLINDUNGAN HAK CIPTA ATAS NOVEL YANG DIBAJAK DAN DIPERJUALBELIKAN DALAM BENTUK BUKU ELEKTRONIK ( E-BOOK ) DI MEDIA SOSIAL (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Duplicate a book into an electronic book or e-book is an exclusive right owned by the creator or copyright owner of the book, therefore. Currently there are many irresponsible people who have duplicated or pirated and sell electronic book versions of novel literature without first asking permission from the author on social media.In accordance with the regulations of the Civil Code, Law Number 28 of 2014 concerning Copyright, and other related laws where violations in the field of copyright of literary works of e-book novels are given strict sanctions The purpose of writing this thesis is, firstly, to find out the forms of harm to novel piracy in the form of e-books on social media and secondly, to find out the resolution efforts that can be made by the copyright owner of the hijacked novels and traded in the form of e-books on social media.This type of research is sociological legal research. This research is more specific to seeing the law in a real sense and examining how the law works in society by analyzing various literatures related to the problem being studied. The research was conducted in Pekanbaru City and on social media Instagram, while the population and sample were Dee Lestari as the author and owner of the Copyright, Instagram account @ebook.squad, and consumers. Data sources used, primary data and secondary data, data collection techniques in this research with interview observation and literature study.From the results of this research, it can be concluded, firstly, the user in the form of an e-book has violated the Moral and Economic Rights of the Copyright Owner because it caused moral and economic losses by making copies without the permission of the Copyright owner and making profits by trading on social media. Second, settlement efforts that can be made by copyright enforcers for hijacked novels and trading in the form of e-books on social media can use two ways.Keywords: Copyright, Piracy, E-book.